RETROSPECTIVE REVIEW OF INJECTION THERAPY IN MORTON'S NEUROMA. Issue 10 (10th June 2013) - Schiffer, G; Chan, O; Jalan, R; Padhiar, N
Abstract : Objective: The objective is to compare the effectiveness of two different methods of administering injection, ultrasound guided versus palpation guided, for the treatment of Morton's Neuroma. Patients and Methods: This is a retrospective review of patients who have had corticosteroid-injections as part of their treatment for Morton's Neuroma. A postal-questionnaire using a modified Foot Health Status Questionnaire, reviewing foot-pain, foot function-activity, footwear and general foot health, was utilised and posted to all patients diagnosed with Morton's Neuroma in the Podiatry Clinic between 2001–2006. No inclusion or exclusion criteria were applied. Results: Of the 104 questionnaires distributed 46 (44.23%) were returned. Subjects who had no corticosteroid injection as treatment for Morton's Neuroma were excluded 14/46 (30.43%). Subsequently 32/46 subjects were evaluated. To some extend better results were demonstrated in the palpation guided injection group. There was some evidence of statistical significance (p=0.05) in three questions. Those were concerning the time interval between the last corticosteroid injection and completion of the questionnaire (0.02), work limitation (p=0.048) or walking (0.0482) difficulties secondary to foot problems. No other statistical association was confirmed. Conclusion: Injection therapy is often the treatment of choice. No advantage has been demonstrated in this survey of ultrasound guided injection versus palpation guided injection. Further studies are needed to prove the effectiveness of ultrasound guided corticosteroid injection.